1998
DOI: 10.3171/foc.1998.4.5.7
|View full text |Cite
|
Sign up to set email alerts
|

Primary intramedullary melanoma

Abstract: Primary intramedullary melanoma is a very rare tumor, most frequently occurring in the middle or lower thoracic spinal cord. The authors present a new case of primary cervical cord melanoma that developed in a 62-year-old man whose tumor was surgically treated and subsequently received radiation therapy. Clinical and histogenetic features of this neoplasm, results of chemo-, radio-, and immunotherapy are reported. Both “disembryogenetic” and “mesodermal” hypotheses on the origin of primary spinal melan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 32 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…Oncogenesis could be dependent on cellular migration-related anomalies. 6 Additionally, primary CNS melanoma in atypical sites may originate from melanoblasts accompanying the pial sheaths of vascular bundles or from neuroectodermal cells with arrested migration during embryogenesis. 2,7 Primary CNS malignant melanomas are rare neoplasms, with an estimated incidence of 0.005 cases per 100,000 people.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Oncogenesis could be dependent on cellular migration-related anomalies. 6 Additionally, primary CNS melanoma in atypical sites may originate from melanoblasts accompanying the pial sheaths of vascular bundles or from neuroectodermal cells with arrested migration during embryogenesis. 2,7 Primary CNS malignant melanomas are rare neoplasms, with an estimated incidence of 0.005 cases per 100,000 people.…”
Section: Discussionmentioning
confidence: 99%
“…4,22 However, other authors have reported favorable outcomes without adjuvant therapy, 20 and have even concluded that primary CNS malignant melanoma is not radiosensitive. 6 In conclusion, awareness of primary intramedullary malignant melanoma is important and this neoplasm needs to be included in the differential diagnosis of spinal cord tumors when appropriate. While imaging plays a major role in the evaluation of this tumor, MRI alone cannot determine the final diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations